Calcined clay – Limestone cements: Hydration processes with high and low-grade kaolinite clays. (29th March 2021) - Cardinaud, Guillemette; Rozière, Emmanuel; Martinage, Olivier; Loukili, Ahmed; Barnes-Davin, Laury; Paris, Michael; Deneele, Dimitri
Highlights: Highly kaolinitic and composite calcined clays combined with Portland cement and limestone. Hydration of clinker enhanced in both binary and ternary binders. Lower pozzolanic reactivity of composite clay. Limestone fostered the reactivity of composite clay. Abstract: The development of ternary binders based on limestone and calcined clays appear as a promising way to increase the substitution of clinker. Their production is likely to remain limited if highly kaolinitic clays are required, but calcined clays with low metakaolin content are less reactive in a binary binder, as shown in many previous studies. This study focused on the difference, regarding hydration degree and products, between several binders containing calcined clay and limestone filler. Two calcined clays were studied, coming from two very different raw clays. The first calcined clay contained more metakaolin than the second one. In addition to ordinary Portland cement, four binders were analysed: two binary blends with 25% of cement substitution by the two calcined clays. Two ternary binders, composed of 30% of calcined clay and 15% of limestone filler, were also studied, using both calcined clays. Binary binders showed strong differences between the two calcined clays. However, this work showed that in a ternary binder, significant pozzolanic activity and synergy between calcined clay and limestone filler were observed even for the composite calcined clay with minor metakaolinite content. From this comprehensive study on hydration, it can be concluded that calcined clay with low metakaolin content is likely to result in the same degree of hydration and products at long-term as high metakaolin calcined clay in a ternary system.